Otimização do processo de extração do óleo essencial de priprioca (Cyperus articulatus L.) por arraste com vapor - CORUMBÁ, Lorena Gomes (Universidade Federal do Pará, 2014)
It is analyzed the process of extraction of the essential oil of priprioca (Cyperus articulatus L.) rhizomes experimentally with water steam, in a prototype in bench scale. Through design of experiments and response surfaces methodology, they are considered the optimal conditions to maximize the response variables yield and mustakone concentration, majority component of the essential oil of priprioca, in function of operational entrance variables of the process. The independent variables and respective levels are: load or mass of priprioca rhizomes, in grams (64, 200, 400, 600, 736); granulometry of the rhizomes, in millimeters (0,61; 1,015; 1,6; 2,19; 2,58) and extraction time, in minutes (44, 60, 90, 120, 140). Using a central composite design, with aid of the application StatisticaR 7.0, mathematical models are proposed for the responses in function of the isolated independent variables and of their combinations. It is verified that the yield in essential oil and the mustakone tenors can be fitted appropriately for second order polynomials models. They are obtained larger yield simultaneously in oil and mustakone tenors, when the load of rhizomes varies from 105 to 400 grams for extraction times between 105 and 140 minutes.